MicroRNAs in spent blastocyst culture medium are derived from trophectoderm cells and can be explored for human embryo reproductive competence assessment - Antonio Capalbo; Filippo Maria Ubaldi; Danilo Cimadomo; Laila Noli; Yakoub Khalaf; Alessio Farcomeni; Duško Ilić; Laura Rienzi (2015)
ObjectiveTo assess whether extracellular microRNAs (miRNAs) can be accurately profiled from spent blastocyst culture media (SBM) and used as embryonic biomarkers.DesignProspective cohort study.SettingPrivate and academic in vitro fertilization centers.Patient(s)Inner cell mass-free trophectoderm (TE) samples and their relative SBM from five good-quality human blastocysts.Intervention(s)Protocol for miRNA purification and analysis based on quantitative polymerase chain reaction set and validated on human embryonic stem cells (hESCs) and on SBM with and without biological variability.Main Outcomes Measure(s)Analysis of miRNAs in culture media in relation with TE cells and comparison of miRNA profiles between implanted and unimplanted euploid blastocysts.Result(s)Culture media from embryos in the cleavage, morula, and blastocyst stages were collected to investigate the presence of miRNAs. The SBM were prospectively collected from euploid implanted (n = 25) and unimplanted blastocysts (n = 28) for comparison. We hypothesized that human embryos secrete miRNAs in culture media that can be used as biomarkers. The comparative analysis of TE and SBM samples revealed that 96.6% (57 of 59; 95 CI, 88.3–99.6) of the miRNAs detected in the SBM were expressed from TE cells, suggesting a TE origin. The culture media collected from cleavage and morula stage embryos showed a pattern similar to blanks, suggesting that miRNAs profiling from spent culture media applies only for blastocysts. MicroRNAs analysis of SBM from euploid implanted and unimplanted blastocysts highlighted two miRNAs (miR-20a, miR-30c) that showed increased concentrations in the former and were predicted in silico to be involved in 23 implantation-related pathways.Conclusion(s)MicroRNAs secreted from human blastocysts in culture media can be profiled with high reproducibility, and this approach can be further explored for noninvasive embryo selection.